On Reading Love in Frankenstein and The Song of Songs - Cameron, Yael (2021)
This essay draws together the Song of Songs and Mary Shelly’s Frankenstein in order to engage in a comparative reading, one text alongside the other. The theoretical frame that holds this rereading is Cixous’s school of poetic thinking-writing: écriture féminine. The contribution this essay makes to studies of the Song of Songs is in its problematising of divine love and critical emphasis on its mortality within a discursive and eclectic world of texts, primarily Frankenstein, but also, Paradise Lost, Genesis, The Book of Promethea, and Philosophy of the Boudoir.
Keywords: Frankenstein; Mary Shelley; Cixous